Islamic Law in National Legal System (Theory of Applicability, Development and Implementation in Indonesia) - Wahyudi, Trubus (Sultan Agung Notary Law Review, 2024)
Indonesia is a country of law based on Pancasila and the 1945 Constitution of the Republic of Indonesia, upholding ethical values and moral values, as well as the noble personality of the nation, believing in and being devoted to God Almighty, and respecting diversity in social, national and state life, and protecting the dignity and honor of every citizen. The Unitary State of the Republic of Indonesia also aims to realize an orderly, clean, prosperous and orderly life in the life of the nation, state and society. ExistenceIslamic law is closely related to the Islamic religion which is always interesting to study and discuss, because the majority of the population of Indonesia is Muslim. Because Islamic law always follows and cannot be separated at all from the "Principle of Islamic Personality" where people who adhere to Islam are located. The existence of Islamic law has long been understood as an inseparable part of the awareness of Indonesian society regarding law and justice, the existence of which is clear within the framework of contribution as raw material for national law, even as a form of transformation of Islamic law into the national legal system.